ANALISIS STRATEGI PEMASARAN INTERNASIONAL PADA PT INDOFOOD CBP SUKSES MAKMUR TBK (ICBP) - Elimawaty Rombe; Welimas Kristina Parinsi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Indofood CBP Sukses Makmur Tbk (ICBP) is a company that is one of the largest companies in Indonesia. This company operates in the field of producing types of food and beverages such as processed instant noodles, milk, processed snacks, food flavorings, and nutritious food and drinks. PT Indofood CBP has products that have penetrated the international market, especially its most famous product, Indomie instant noodles. Even PT Indofood CBP is also known to have established instant noodle factories in several countries around the world. The purpose of this research is to find out and analyze the international strategy applied in PT Indofood CBP Sukses Makmur (ICBP). The research method used in this research used in this research is descriptive qualitative. The results of the research found indicate that the international marketing strategy used by PT Indofood CBP is a licensing and joint venture strategy. It can be concluded that PT Indofood CBP is able to market its superior product, namely Indomie, which is fast food and is liked by many people in other parts of the world by implementing the right strategy.